The rebellion of Muhammad al-Nafs al-Zakiyya in 145/762 : Ṭālibīs and early ʻAbbāsids in conflict - Elad, Amikam. (Islamic History and Civilization, 2016)
This book presents a detailed in-depth study, primarily based on primary Arabic sources, of the background, history and the consequences of the rebellion of Muhammad born ʿAbdallah born al-Hasan born al-Hasan born ʿAli born Abi Talib, better known as al-Nafs al-Zakiyya, in 145/762, during the reign of the Abbasid Caliph, Abu Jaʿfar al-Mansur. It focuses on the relations between the early Abbasid and the different Talibi-(Shiʿi) families - mainly the Hasanis and the Husaynis - and the internal struggles between these factions for the legitimacy of authority.